EFEKTIVITAS PROGRAM KONSELING REMAJA DI DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA KOTA MANADO - ABUBAKAR, MIRNA; RURU, JOORIE; LONDA, VERY (Sam Ratulangi University, 2020)
Adolescence is a transition from children to adulthood. Teenagers' lives are crucial for their future lives. This study aims to determine the effectiveness of youth counseling programs in the City of Manado population and family planning control agency. This research uses descriptive qualitative research type. Data collection techniques used were observation, interviews and documentation. The effectiveness of the Youth Counseling Program in Manado City is still not good. In terms of indicators in accordance with the research focus of researchers, namely the objectives, integration, and adaptation of the implementers of this program. It can be seen that this program has clear objectives in accordance with what is stated in the 1945 Constitution and Law no. 52 of 2009 so it needs to be seen also whether it is well integrated and able to adapt.Keywords: Effectiveness, Youth Counseling Program